Evaluations of NSAIDs and Opioids as Analgesics in Pediatric Oncology - Eduardo Ladeia Leal; Paulo Caleb Júnior Lima Santos; Thuane Sales Gonçalves; Mariana Martins Gonzaga do Nascimento; Fábio Cardoso Cruz; Flávia Borelli Gomes do Nascimento; Carolina Paula Jesus Kasa (MDPI AG, 2023)
As one of the leading causes of death in childhood, cancer also causes discomfort to pediatric patients. Even with guidelines for pain management, more than half of hospitalized children have intense and unrelieved pain. The present work aims to describe the intensity of pain and its pharmacological management in a pediatric oncology population. Patients aged 0 to 17 years old, diagnosed with cancer, who were admitted to a children's oncology hospital and had well-documented data on pain management in their medical records were included. A total of 333 patients were included, mostly male (55.8%) with a mean age of 7.9 years. A substantial portion of the patient cohort (51.4%) initially reported experiencing pain of moderate intensity during the first assessment. Subsequently, following the pharmacological intervention, a significant proportion of patients (90.1%) reported complete alleviation of pain. The predominant pharmaceutical agents utilized for pain management encompassed metamizole (76.6%) and morphine (10.2%). All pharmacological interventions used were able to significantly reduce patients' pain. This study underscores the utilization of different pharmacological classes to achieve notable reductions in pain intensity among patients grappling with severe pain.